Tourism Logistics Factors Affecting Wellness Tourism in Phuket - Supradit, Athita; Suthiwartnarueput, Kamonchanok (Journal of Thai Hospitality and Tourism, 2025)
The objectives of this research were to study tourism logistics factors affecting wellness tourists in Phuket province, to analyze and rank the importance and satisfaction levels of these tourists towards tourism logistics, and to propose recommendations for the development and improvement of health–focused tourism logistics management in Phuket. Data were collected via questionnaires and analyzed using the IPA technique. The samples were divided into three groups: 140 foreign health–oriented tourists, 18 health business operators, and 5 other related parties. The results found that (1) most of the tourists were of working age, educated, self–employed, or employees of companies, with a fairly high to high income, mostly from Europe and America. (2) These tourists prioritized tourism logistics factors in every aspect, such as personnel, finance, services in health establishments, physical aspects, tourist locations, and information/news, respectively. (3) Tourists had the highest satisfaction level with tourism logistics in the financial, personnel, and tourist location aspects, respectively. (4) The necessary tourism logistics factors that needed urgent improvement were overall service in establishments and minor factors, such as travel connectivity and the public transportation system in Phuket province.